(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The study presents the notion of „national education” as Gyula Gömbös and other leaders of his Party used it. The question is how they used propaganda for forming the way of thinking of the society and why the notion emerged among their political tools. Another question is how Bálint Hóman uses the same notion for his educational politics especially in respect of the legal regulations of the time. It is to be seen that the aims, principles and values formed by Gömbös and his Party are to be identified in Hóman’s practical educational regulations during the time when he was the Minister of Culture.